Casketball capers - Bently, Peter; Harrison, Chris (Chicago, Ill. : Albert Whitman, 2011)
When the students of St. Orlok's Elementary School for Vampires face a cheating werewolf in a game of casketball, nine-year-old Lee Price asks his friend, Boris the bat, for help.
"First published in Great Britain in 2010 by Boxer Books Limited"--P. facing t.p.
Gr. 2-3.
560
Accelerated Reader AR
Keywords: Ball games -- Fiction; Sports -- Corrupt practices -- Juvenile fiction; Cheating -- Fiction; Schools -- Fiction; Vampires -- Fiction; Werewolves -- Fiction; Bats -- Fiction